Commentary - In silico acute oral toxicity models are fit for inclusion in GHS and DG Model regulations classification criteria - Matthew Schmitz; Joel Bercu; Jessica Graham; Kamila Blum; Jedd Hillegass; Candice Johnson; Robert Jolly; Pamela Kramer; Kamel Mansouri; Melisa Masuda-Herrera; Chandrika Moudgal; Eva Ogorevc; et al. (Regulatory Toxicology and Pharmacology, 2026)

Fifty years of riverine harmful algal bloom modeling: A global synthesis of approaches, challenges, and opportunities - Jennifer C. Murphy; Rebecca M. Gorney; Lisa V. Lucas; Jacob A. Zwart; Jennfier L. Graham (Water Research, 2026)

Coral rubble facilitates feeding opportunities for invertivorous reef fishes on tropical coral reefs - Lisa S. Goberdhan; Gareth J. Williams; Shaun K. Wilson; Rodney Melanie; Nicholas A. J. Graham (Coral Reefs, 2026)
Invertivorous reef fishes play a crucial role in coral reef ecosystems, transferring energy from benthic invertebrates to higher trophic levels. They rely on a diverse array of benthic habitats to forage for invertebrate prey. However, climate change and local stressors are reshaping reef habitats, with coral rubble becoming increasingly dominant. Despite low structural complexity, coral rubble supports abundant invertebrates, presenting both opportunities and challenges for invertivorous fish. However, the foraging ecology of fish in rubble habitats remains understudied, limiting our ability to predict their responses to ongoing reef degradation. By combining 28 yrs of reef fish and benthic community monitoring data with targeted rubble disturbance and fish foraging experiments on reefs in the inner Seychelles Islands, we test whether invertivorous reef fish community structure on coral rubble habitats is influenced by reefs characterised by distinct benthic regimes (rubble-dominated, hard substrate-dominated or macroalgal dominated) and by opportunistic feeding mechanisms. We show that invertivorous reef fish communities are highly distinct among benthic regimes at the reef scale, and benthic regime influences the invertivorous reef fish community associated with static, unconsolidated rubble habitats. However, when unconsolidated rubble habitats are physically disturbed, differences among benthic regimes diminish, and a consistent subset of invertivorous fishes rapidly exploit rubble habitats across regimes. These findings are important in shaping our understanding of how reef fish communities may interact with future reef environments, and the species that may have a competitive advantage on rubble-dominated reefs, influencing trophic interactions and resource use.

High thermotolerance to extreme marine heatwaves for four New Caledonian sponges - Barbara J. Graham; Simon K. Davy; Lisa Woods; Torsten Thomas; Riccardo Rodolfo-Metalpa; James J. Bell (Marine Pollution Bulletin, 2026)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Nature and Distribution of Beach Ridges on the Islands of the Greater Caribbean - Anna Lisa Cescon; James Andrew Graham Cooper; Derek W. T. Jackson (Journal of Marine Science and Engineering, 2024)
Beach ridges originate from various depositional processes and occur in a variety of settings. This paper assesses their nature and distribution on the islands of the Greater Caribbean based on a literature review and the identification of sites using Google Earth© 7.3 imagery. The morphological and orientation parameters were measured for each site, and a measure of storm density was developed. These were statistically analysed to develop a classification of beach ridge types. The results show a diversity of beach ridge systems, in terms of setting, morphology, composition and preservation. The presence or absence of an adjacent coral reef is a major differentiating element at the regional level. A regional beach ridge plain classification is proposed, including two main classes, marine beach ridges and river-associated beach ridges, with further sub-divisions based on exposure to hurricanes or hurricanes plus swell waves.

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Ocular microtremor: a structured review - Lisa Graham; Julia Das; Rodrigo Vitorio; Claire McDonald; Richard Walker; Alan Godfrey; Rosie Morris; Samuel Stuart (Experimental Brain Research, 2023)
Ocular microtremor (OMT) is the smallest of three involuntary fixational micro eye movements, which has led to it being under researched in comparison. The link between OMT and brain function generates a strong rationale for further study as there is potential for its use as a biomarker in populations with neurological injury and disease. This structured review focused on populations previously studied, instrumentation used for measurement, commonly reported OMT outcomes, and recommendations concerning protocol design and future studies. Current methods of quantifying OMT will be reviewed to analyze their efficacy and efficiency and guide potential development and understanding of novel techniques. Electronic databases were systematically searched and compared with predetermined inclusion criteria. 216 articles were identified in the search and screened by two reviewers. 16 articles were included for review. Findings showed that piezoelectric probe is the most common method of measuring OMT, with fewer studies involving non-invasive approaches, such as contact lenses and laser imaging. OMT frequency was seen to be reduced during general anesthesia at loss of consciousness and in neurologically impaired participants when compared to healthy adults. We identified the need for a non-invasive technique for measuring OMT and highlight its potential in clinical applications as an objective biomarker for neurological assessments. We highlight the need for further research on the clinical validation of OMT to establish its potential to identify or predict a meaningful clinical or functional state, specifically, regarding accuracy, precision, and reliability of OMT.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Ecological-Fishery Forecasting of Squid Stock Dynamics under Climate Variability and Change: Review, Challenges, and Recommendations - Hassan Moustahfid; Lisa C. Hendrickson; Alexander Arkhipkin; Graham J. Pierce; Avijit Gangopadhyay; Hideaki Kidokoro; Unai Markaida; Chingiz Nigmatullin; Warwick H. Sauer; Patrizia Jereb; Gretta Pecl; Thibaut de la Chesnais; et al. (Reviews in Fisheries Science & Aquaculture, 2021)

Low‐coverage genomic data resolve the population divergence and gene flow history of an Australian rain forest fig wasp - Lisa Cooper; Lynsey Bunnefeld; Jack Hearn; James M. Cook; Konrad Lohse; Graham N. Stone (Molecular Ecology, 2020)
Population divergence and gene flow are key processes in evolution and ecology. Model‐based analysis of genome‐wide data sets allows discrimination between alternative scenarios for these processes even in nonmodel taxa. We used two complementary approaches (one based on the blockwise site frequency spectrum [bSFS], the second on the pairwise sequentially Markovian coalescent [PSMC]) to infer the divergence history of a fig wasp, Pleistodontes nigriventris . Pleistodontes nigriventris and its fig tree mutualist Ficus watkinsiana are restricted to rain forest patches along the eastern coast of Australia and are separated into The Northern population is to the north of the Southern populations by two dry forest corridors (the Burdekin and St. Lawrence Gaps). We generated whole genome sequence data for two haploid males per population and used the bSFS approach to infer the timing of divergence between northern and southern populations of P. nigriventris , and to discriminate between alternative isolation with migration (IM) and instantaneous admixture (ADM) models of postdivergence gene flow. Pleistodontes nigriventris has low genetic diversity (π = 0.0008), to our knowledge one of the lowest estimates reported for a sexually reproducing arthropod. We find strongest support for an ADM model in which the two populations diverged ca . 196 kya in the late Pleistocene, with almost 25% of northern lineages introduced from the south during an admixture event ca. 57 kya. This divergence history is highly concordant with individual population demographies inferred from each pair of haploid males using PSMC. Our analysis illustrates the inferences possible with genome‐level data for small population samples of tiny, nonmodel organisms and adds to a growing body of knowledge on the population structure of Australian rain forest taxa.

Increasing the Production Efficiency of Potato with Plant Growth Retardants - Graham D. Ellis; Lisa O. Knowles; N. Richard Knowles (American Journal of Potato Research, 2020)

Conducting groundwater monitoring studies in Europe for pesticide active substances and their metabolites in the context of Regulation (EC) 1107/2009 - Anne Louise Gimsing; Jutta Agert; Nicole Baran; Arnaud Boivin; Federico Ferrari; Richard Gibson; Lisa Hammond; Florian Hegler; Russell L. Jones; Wolfram König; Jenny Kreuger; Ton van der Linden; et al. (Journal of Consumer Protection and Food Safety, 2019)

The Microbiota, Immunoregulation, and Mental Health: Implications for Public Health - Christopher A. Lowry; David G. Smith; Philip H. Siebler; Dominic Schmidt; Christopher E. Stamper; James E. Hassell; Paula S. Yamashita; James H. Fox; Stefan O. Reber; Lisa A. Brenner; Andrew J. Hoisington; Teodor T. Postolache; et al. (Current Environmental Health Reports, 2016)

Association of single nucleotide polymorphisms with form traits in three New Zealand populations of radiata pine in the presence of genotype by environment interactions - Yongjun Li; Phillip Wilcox; Emily Telfer; Natalie Graham; Lisa Stanbra (Tree Genetics & Genomes, 2016)

Genome-wide association of familial prostate cancer cases identifies evidence for a rare segregating haplotype at 8q24.21 - Craig C. Teerlink; Daniel Leongamornlert; Tokhir Dadaev; Alun Thomas; James Farnham; Robert A. Stephenson; Shaun Riska; Shannon K. McDonnell; Daniel J. Schaid; William J. Catalona; S. Lilly Zheng; Kathleen A. Cooney; et al. (Human Genetics, 2016)

The effects of height and BMI on prostate cancer incidence and mortality: a Mendelian randomization study in 20,848 cases and 20,214 controls from the PRACTICAL consortium - Neil M. Davies; Tom R. Gaunt; Sarah J. Lewis; Jeff Holly; Jenny L. Donovan; Freddie C. Hamdy; John P. Kemp; Rosalind Eeles; Doug Easton; Zsofia Kote-Jarai; Ali Amin Al Olama; Sara Benlloch; et al. (Cancer Causes & Control, 2015)

Oral and inhaled p38 MAPK inhibitors: effects on inhaled LPS challenge in healthy subjects - Dave Singh; Leonard Siew; Jared Christensen; Jonathan Plumb; Graham W. Clarke; Steve Greenaway; Christelle Perros-Huguet; Nick Clarke; Iain Kilty; Lisa Tan (European Journal of Clinical Pharmacology, 2015)

World Squid Fisheries - Alexander I. Arkhipkin; Paul G. K. Rodhouse; Graham J. Pierce; Warwick Sauer; Mitsuo Sakai; Louise Allcock; Juan Arguelles; John R. Bower; Gladis Castillo; Luca Ceriola; Chih-Shin Chen; Xinjun Chen; et al. (Reviews in Fisheries Science & Aquaculture, 2015)

Association analysis of 9,560 prostate cancer cases from the International Consortium of Prostate Cancer Genetics confirms the role of reported prostate cancer associated SNPs for familial disease - Craig C. Teerlink; Stephen N. Thibodeau; Shannon K. McDonnell; Daniel J. Schaid; Antje Rinckleb; Christiane Maier; Walther Vogel; Geraldine Cancel-Tassin; Christophe Egrot; Olivier Cussenot; William D. Foulkes; Graham G. Giles; et al. (Human Genetics, 2014)

HOXB13 is a susceptibility gene for prostate cancer: results from the International Consortium for Prostate Cancer Genetics (ICPCG) - Jianfeng Xu; Ethan M. Lange; Lingyi Lu; Siqun L. Zheng; Zhong Wang; Stephen N. Thibodeau; Lisa A. Cannon-Albright; Craig C. Teerlink; Nicola J. Camp; Anna M. Johnson; Kimberly A. Zuhlke; Janet L. Stanford; et al. (Human Genetics, 2013)

Validation of prostate cancer risk-related loci identified from genome-wide association studies using family-based association analysis: evidence from the International Consortium for Prostate Cancer Genetics (ICPCG) - Guangfu Jin; Lingyi Lu; Kathleen A. Cooney; Anna M. Ray; Kimberly A. Zuhlke; Ethan M. Lange; Lisa A. Cannon-Albright; Nicola J. Camp; Craig C. Teerlink; Liesel M. FitzGerald; Janet L. Stanford; Kathleen E. Wiley; et al. (Human Genetics, 2012)

Genetic background modulates behavioral impairments in R6/2 mice and suggests a role for dominant genetic modifiers in Huntington’s disease pathogenesis - Randi-Michelle Cowin; Nghiem Bui; Deanna Graham; Jennie R. Green; Lisa A. Yuva-Paylor; Andreas Weiss; Richard Paylor (Mammalian Genome, 2012)

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Silviculture and Forest Ecology - David Mercker; Ryan Blair; Don Tyler; Theresa Jain; Russell Graham; Donald Rockwood; Nicholas Koch; Jeremy Brawner; Omar Carrero; Kristofer Covey; Alex Barrett; Mark Ashton; et al. (Journal of Forestry, 2011)
2Over the past several decades, federal incentive programs have encouraged the restoration of bottomland forests throughout the West Gulf Coastal Plain (WGCP) and the Lower Mississippi Alluvial Valley (LMAV). Programs such as the Conservation Reserve (CRP) and Wetlands Reserve (WRP) Programs have been marginally successful (Stanturf et al. 2001). Foresters and contractors often follow conventional tree planting procedures that are well established for upland sites, but prove problematic in bottomlands. High water tables, soil drainage and compaction, overland flooding and diverse soil properties make species selection difficult. Slight changes in topography and soil structure often have a dramatic effect on survival and growth of planted oak seedlings (Hodges and Schweitzer 1979). This project documented the survival and growth of six-year old seedlings that were established on a bottomland site in 2004, located at the West Tennessee Research and Education Center, Jackson, Tennessee. The purpose was to determine how soil drainage as indicated by mottling (specifically, the point of 50 percent gray color throughout the soil profile) affects the survival and growth of bottomland oak species. The findings suggest that practitioners plant Nuttall, pin and overcup oaks in poorly drained soils. As the drainage improves, begin mixing in willow oak. In the best drained soils (if they exist), finish by including water, swamp chestnut, swamp white, Shumard, cherrybark and bur oaks. Potential species diversity should expand as the soil drainage improves.

Displacement, velocity preference, and substrate use of three native California stream fishes in simulated pulsed flows - Stephanie N. Chun; Sarah A. Cocherell; Dennis E. Cocherell; Javier B. Miranda; Gardner J. Jones; Justin Graham; A. Peter Klimley; Lisa C. Thompson; Joseph J. Cech (Environmental Biology of Fishes, 2011)

Pooled analyses of 13 prospective cohort studies on folate intake and colon cancer - Dong-Hyun Kim; Stephanie A. Smith-Warner; Donna Spiegelman; Shiaw-Shyuan Yaun; Graham A. Colditz; Jo L. Freudenheim; Edward Giovannucci; R. Alexandra Goldbohm; Saxon Graham; Lisa Harnack; Eric J. Jacobs; Michael Leitzmann; et al. (Cancer Causes & Control, 2010)

A Model-Based Methodology for Spray-Drying Process Development - Dan E. Dobry; Dana M. Settell; John M. Baumann; Rod J. Ray; Lisa J. Graham; Ron A. Beyerinck (Journal of Pharmaceutical Innovation, 2009)

Marble burying reflects a repetitive and perseverative behavior more than novelty-induced anxiety - Alexia Thomas; April Burant; Nghiem Bui; Deanna Graham; Lisa A. Yuva-Paylor; Richard Paylor (Psychopharmacology, 2009)

Effect of anti-fibrinolytic therapy on experimental melanoma metastasis - Jennifer M. Kirstein; Kevin C. Graham; Lisa T. MacKenzie; Danielle E. Johnston; Leslie J. Martin; Alan B. Tuck; Ian C. MacDonald; Ann F. Chambers (Clinical & Experimental Metastasis, 2009)

In Vivo Phage Display to Identify M Cell-Targeting Ligands - Lisa M. Higgins; Imelda Lambkin; Graham Donnelly; Daragh Byrne; Carolyn Wilson; Jacqueline Dee; Melanie Smith; Daniel J. O'Mahony (Pharmaceutical Research, 2004)

Adolescent diet and risk of breast cancer - A. Lindsay Frazier; Lisa Li; Eunyong Cho; Walter C. Willett; Graham A. Colditz (Cancer Causes & Control, 2004)

MIC-A allele profiles and HLA class I associations in Behçet's disease - Graham R. Wallace; David H. Verity; Lisa J. Delamaine; Shigeaki Ohno; Hidetoshi Inoko; Masao Ota; Nobuhisa Mizuki; Kazuro Yabuki; Elli Kondiatis; Henry A. F. Stephens; Wafa Madanat; Charles A. Kanawati; et al. (Immunogenetics, 1999)

Unprecedented Low Levels of Genetic Variation and Inbreeding Depression in an Island Population of the Black‐Footed Rock‐Wallaby - Mark D. B. Eldridge; Juliet M. King; Anne K. Loupis; Peter B. S. Spencer; Andrea C. Taylor; Lisa C. Pope; Graham P. Hall (Conservation Biology, 1999)
It has been argued that demographic and environmental factors will cause small, isolated populations to become extinct before genetic factors have a significant negative impact. Islands provide an ideal opportunity to test this hypothesis because they often support small, isolated populations that are highly vulnerable to extinction. To assess the potential negative impact of isolation and small population size, we compared levels of genetic variation and fitness in island and mainland populations of the black‐footed rock‐wallaby ( Petrogale lateralis [Marsupialia: Macropodidae]). Our results indicate that the Barrow Island population of P. lateralis has unprecedented low levels of genetic variation ( H e = 0.053, from 10 microsatellite loci) and suffers from inbreeding depression (reduced female fecundity, skewed sex ratio, increased levels of fluctuating asymmetry). Despite a long period of isolation ( ∼ 1600 generations) and small effective population size ( N e ∼ 15), demographic and environmental factors have not yet driven this population to extinction. Nevertheless, it has been affected significantly by genetic factors. It has lost most of its genetic variation and become highly inbred ( F e = 0.91), and it exhibits reduced fitness. Because several other island populations of P. lateralis also exhibit exceptionally low levels of genetic variation, this phenomenon may be widespread. Inbreeding in these populations is at a level associated with high rates of extinction in populations of domestic and laboratory species. Genetic factors cannot then be excluded as contributing to the extinction proneness of small, isolated populations.